Reversal of CSF HIV-1 Escape during Treatment of HIV-Associated Cryptococcal Meningitis in Botswana - Nametso Kelentse; Sikhulile Moyo; Kesaobaka Molebatsi; Olorato Morerinyane; Shatho Bitsang; Ontlametse T. Bareng; Kwana Lechiile; Tshepo B. Leeme; David S. Lawrence; Ishmael Kasvosve; Rosemary Musonda; Mosepele Mosepele; et al. (Biomedicines, 2022)
Cerebrospinal fluid (CSF) viral escape has been poorly described among people with HIV-associated cryptococcal meningitis. We determined the prevalence of CSF viral escape and HIV-1 viral load (VL) trajectories in individuals treated for HIV-associated cryptococcal meningitis. A retrospective longitudinal study was performed using paired CSF and plasma collected prior to and during the antifungal treatment of 83 participants recruited at the Botswana site of the phase-3 AMBITION-cm trial (2018–2021). HIV-1 RNA levels were quantified then CSF viral escape (CSF HIV-1 RNA ≥ 0.5 log10 higher than plasma) and HIV-1 VL trajectories were assessed. CSF viral escape occurred in 20/62 (32.3%; 95% confidence interval [CI]: 21.9–44.6%), 13/52 (25.0%; 95% CI: 15.2–38.2%) and 1/33 (3.0%; 95% CI: 0.16–15.3%) participants at days 1, 7 and 14 respectively. CSF viral escape was significantly lower on day 14 compared to days 1 and 7, p = 0.003 and p = 0.02, respectively. HIV-1 VL decreased significantly from day 1 to day 14 post antifungal therapy in the CSF but not in the plasma (β = −0.47; 95% CI: −0.69 to −0.25; p < 0.001). CSF viral escape is high among individuals presenting with HIV-associated cryptococcal meningitis; however, antifungal therapy may reverse this, highlighting the importance of rapid initiation of antifungal therapy in these patients.